Fabrication of poly(ϵ‐caprolactone)/paclitaxel (core)/chitosan/zein/multi‐walled carbon nanotubes/doxorubicin (shell) nanofibers against MCF‐7 breast cancer. (17th November 2022) - Bahmani, Ehsan; Dizaji, Babak Faraji; Talaei, Sam; Koushkbaghi, Shahnaz; Yazdani, Hamid; Abadi, Parvaneh Ghaderi‐shekhi; Akrami, Mohammad; Shahrousvand, Mohsen; Jazi, Fariborz Sharifian; Irani, Mohammad
Abstract: In the present study, paclitaxel (PTX), multi‐walled carbon nanotubes (MWCNTs), and doxorubicin (DOX) have been simultaneously doped into the poly(ϵ‐caprolactone) (PCL)/chitosan/zein core‐shell nanofibers to increase its cytotoxicity for MCF‐7 breast cancers killing. The physico‐chemical properties of synthesized nanofibers were determined by scanning electron microscope, Fourier‐transform infrared spectroscopy, tensile strength, and degradation rate determinations. The in vitro release studies demonstrated the sustained release of drugs from core‐shell nanofibrous scaffold. The cytotoxicity and compatibility of core‐shell nanofibers were investigated by their treating with MCF‐7 breast cancer cells and L929 normal cells, respectively. PCL/PTX/chitosan/zein/MWCNTs/DOX core‐shell nanofibers containing 1 wt% MWCNTs, 100 μg ml −1 DOX and 100 μg ml −1 PTX had a high biocompatibility with a 84% MCF‐7 cancer cells killing. The in vivo studies revealed the synergic effects of MWCNTs and anticancer drugs on the tumor inhibition. This method could be considered as a new way for developing of MWCNTs loaded‐nanofibers for cancer treatment in future.